Comfort During Non-invasive Ventilation - Cammarota, Gianmaria; Simonte, Rachele; De Robertis, Edoardo (Frontiers in Medicine, 2022)
Non-invasive ventilation (NIV) has been shown to be effective in avoiding intubation and improving survival in patients with acute hypoxemic respiratory failure (ARF), when compared to conventional oxygen therapy. However, NIV is associated with high failure rates due, in most cases, to patient discomfort. Therefore, increasing attention has been paid to all those interventions aimed at enhancing patient’s tolerance to NIV. Several practical aspects have been considered to improve patient adaptation. In particular, the choice of the interface and the ventilatory setting adopted for NIV play a key role in the success of the respiratory assistance. Among the different NIV interfaces, tolerance is poorest for the nasal and oronasal masks, while helmet appears to be better tolerated, resulting in longer use and lower NIV failure rates. The choice of fixing system also significantly affects patient comfort due to pain and possible pressure ulcers related to the device. The ventilatory setting adopted for NIV is associated with varying degrees of patient comfort: patients are more comfortable with pressure-support ventilation (PSV) than controlled ventilation. Furthermore, the use of electrical activity of the diaphragm driven ventilation has been demonstrated to improve patient comfort compared to PSV, while reducing neural drive and effort. If non-pharmacological remedies fail, sedation can be employed to improve patient’s tolerance to NIV. Sedation facilitates ventilation, reduces anxiety, promotes sleep and modulates physiological responses to stress. Judicious use of sedation may be an option to increase the chances of success in some patients at risk for intubation because of NIV intolerance consequent to pain, discomfort, claustrophobia, or agitation. During COVID-19 pandemic, NIV has been extensively employed to face off the massive request of ventilatory assistance. Prone positioning in non-intubated awake COVID-19 patients may improve oxygenation, reduces work of breathing, and, possibly, prevents intubation. Despite these advantages, maintaining prone position can be particularly challenging because poor comfort has been described as main cause of prone position discontinuation. In conclusion, comfort is one of the major determinants of NIV success. All the strategies aimed to increase comfort during NIV should be pursued.